2021
DOI: 10.1177/0954406221989378
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on significance of wave amplitude, wavelength and aspect ratio on heat transfer and fluid flow characteristics in circular wavy MC heat sink design

Abstract: In this study, hydrothermal characteristics in a circular wavy microchannel (CWMC) design under laminar flow conditions with uniform heat flux is numerically studied. Parametric studies in an innovative CWMC design were carried out at various wave amplitudes, wavelengths and aspect ratios. Three dimensional numerical study was performed in the Reynolds number (Re) range from 100 to 300 with uniform heat flux (50 W/cm2) applied at bottom of the channel, treating copper as channel material and water as working f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Due to this kind of structure, pressure drop reduction occurred in combination with the permeation effect and the slip effect of the coolant. Recently, Kumar et al 78 concluded that circular wavy microchannel with higher wave amplitude (0.45 mm), smaller wavelength (5 mm), and smaller aspect ratio ( AR = 2) gave higher heat transfer efficiency with corresponding pressure drop. Nemati et al 77 implemented the multi‐objective genetic algorithm.…”
Section: Channel Patternmentioning
confidence: 99%
“…Due to this kind of structure, pressure drop reduction occurred in combination with the permeation effect and the slip effect of the coolant. Recently, Kumar et al 78 concluded that circular wavy microchannel with higher wave amplitude (0.45 mm), smaller wavelength (5 mm), and smaller aspect ratio ( AR = 2) gave higher heat transfer efficiency with corresponding pressure drop. Nemati et al 77 implemented the multi‐objective genetic algorithm.…”
Section: Channel Patternmentioning
confidence: 99%
“…Dean number: It represents the ratio of product of inertial force and centripetal force to the viscous force. The local Dean number 26 can be given as…”
Section: Computational Model and Numerical Proceduresmentioning
confidence: 99%
“…It represents the ratio of product of inertial force and centripetal force to the viscous force. The local Dean number 26 can be given as Dexgoodbreak=RexDhx2Rc where R c = radius of curvature.…”
Section: Computational Model and Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A Nu improvement of 39% was obtained with the newly introduced design of wavy channels when compared to SWMCs. Further, 13 parametric analysis was carried out for CWMCs by varying the aspect ratios, wave amplitudes, and wavelengths to compare thermal performance with SWMCs. The results revealed that microchannels with lesser wavelength, higher wave amplitude, and lower aspect ratio yield better thermal performance.…”
Section: Introductionmentioning
confidence: 99%